Efeito do ferro em soluções tamponadas, a diferentes valores de pH, sobre a solubilização na apatita-de-Araxá - Martins, Orlando Carlos; Almeida Viegas, Ricardo; Ferreira de Novais, Roberto; Ribeiro, Antônio Carlos (Revista Ceres, 2025)
«Araxd» apatite, in samples of 0.5 g, was shaken for five hours with 25 ml of NaOAc buffered solutions at three pH values (2.5, 3.0 and 3.5) and presenting eight levels of iron (0.0, 5.0, 10.0, 20.0, 40.0, 80.0, 160.0 and 320.0 ug/ml) in three replications and then centrifuged, determining Fe, P and Ca in the supernatant.